Socialization and Training for ISBN Book Creation for the Community in Collaboration with YPAD Publisher - Kurniawan, Angga; Tasrim; Tyagita Dianingtias Sudibyo; Epsilandri Septyarini; Ansri Jayanti (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The "Socialization and Training for ISBN Book Creation to the Community in Collaboration with YPAD Publisher" program aims to enhance literacy and writing skills among the community through book publishing with ISBN. This program involves a series of intensive training, interactive workshops, and individual mentoring sessions designed to guide participants from the writing phase to the publication of their books. With 150 participants, including novice writers, educators, and community leaders, the program successfully improved writing, editing, and book design skills for 120 individuals who completed the training. A total of 50 books were published with ISBNs, demonstrating the program’s success in supporting the comprehensive book publishing process.